A pilot clinical trial on a Variable Automated Speed and Sensing Treadmill (VASST) for hemiparetic gait rehabilitation in stroke patients - Chua, Karen; Chee, Johnny; Wong, Chin Jung; Lim, Pang Hung; Lim, Wei Sheong; Hoo, Chuan Mien; Ong, Wai Sing; Shen, Mira L.; Yu, Wei Shin (Frontiers in Neuroscience, 2015)
Introduction Impairments in walking speed and quantity are common mobility-related problems after stroke. Treadmill training is a useful and accepted method to improve endurance and gait speed. Standard treadmills currently lack variable training speed and automated safe speed progression, thus risking backward displacement and falls. A Variable Automated Speed and Sensing Treadmill (VASST) was thus developed and tested on chronic stroke subjects in a supervised exercise programme. Materials and Methods An open label study with assessor blinding was conducted in 10 community-dwelling chronic hemiplegics who could ambulate at least 0.1m/s for >150 meters with contact guard or supervision. Interventions included physiotherapist-supervised training on VASST for 60 minutes 3 times per week for 4 weeks (total 12 hours). Outcome measures of gait speed, quantity, balance and adverse events were assessed at 0, 2, 4 and 8 weeks. Results Altogether 10 subjects (8 males, mean age 55.5 years, 2.1 years poststroke) completed VASST training. Mean 10-meter walk test speed was 0.69m/s (SD 0.29) and mean 6-minute walk test distance was 178.3m (84.0). After 4 weeks of training, 70% had significant positive gains in gait speed (0.06 m/s SD 0.08m/s, P =0.037); and 90% improved in walking distance. (54.3m, SD 30.9m, P = 0.005). Both gains maintained at week 8. (0.12 m/s SD 0.1, P = 0.01; 56.0m, SD 31.8, P = 0.005). There were no adverse events. Discussion and conclusion This preliminary study demonstrates the initial feasibility and short-term efficacy of VASST for walking speed and distance for chronic stroke with hemiplegia.